Security constrained optimal power flow solution for practical transmission grid using hybrid use of generating plant and network restructuring - Bhoori Singh; Avdhesh Sharma; Akhil Ranjan Garg; Om Prakash Mahela; Baseem Khan; Ahmed Ali (Discover Applied Sciences)
Abstract This paper presented a study on the security constrained optimal power flow (SCOPF) of a practical transmission utility grid network (TUGN). The objectives of reduction in the transmission losses of TUGN (TLGN) and to minimize the bus voltage deviations (BVD) are achieved by addition of thermal power plant (TPP) and network restructuring (NR). Identification of best fit node for generation injection is achieved using the method based on hybrid combination of analytic approach and genetic algorithm (GA). Efficacy of the proposed study is evaluated using the computation of energy equivalent to network loss saving, percentage derating of the load (PDOL), voltage profile, bus voltage deviations, and financial analysis (FA). Study is performed without and with contingency (N-1) for the base case network, TUGN with addition of TPP and TUGN with addition of TPP and NR. This is established that addition of TPP, addition of TPP with NR are effective to reduce the TLGN, improve the voltage profile and minimize the bus voltage deviations. This study is more efficient compared to various studies reported in literature.